(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to determine the attitude and knowledge levels of the students of Harran University Faculty of Dentistry about novel coronavirus disease (COVID-19) and to evaluate their thoughts on distance education.Materials and Methods: An online questionnaire about COVID-19 was conducted to students studying in the Faculty of Dentistry (n=144). The questionnaire consisted of a series of questions such as the demographic features of dentistry students, their degree of knowledge about COVID-19, where they got this information, methods of protection related to COVID-19, their psychological status during this pandemic period and their thoughts about the distance education program. The data obtained from the questionnaires were statistically analyzed.Results: This current study consisted of 144 participants (mean age of 20±1.3) including 83 (57.6%) females and 61 (42.4%) males. The majority of the participants (76.4%) stated that they learned information related to COVID-19 from the Ministry of Health, the World Health Organization (WHO), and the Turkish Dental Association (TDA). The most common individual measure was determined ’not to be in crowded environments’ (86.1%). During this period, 124 (86.1%) participants, consisting of 43 (34.7%) male and 81 (65.3%) female, reported that they voluntarily put themselves into quarantine (p0.05). Of 87.5% the participants noted that they thought distance education system implemented due to COVID-19 is not enough. Conclusion: Dental students at Harran University Faculty of Dentistry were aware of the seriousness of the COVID-19 pandemic. Even if this epidemic badly affected their psychology, they would not give up on their profession.